2000
DOI: 10.1097/00005537-200001000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells in Precancerous Lesions of the Larynx

Abstract: Objectives: Hyperplastic lesions of the laryngeal mucosa can eventually develop into squamous cell carcinoma. The relationship between dendritic cell infiltration of head and neck cancers and prognosis is well known. Surprisingly, data regarding dendritic cell infiltration in precancerous lesions are not available today. It was the purpose of our study to extend these observations and to investigate in more detail the density and distribution of dendritic cells in precancerous lesions. Study Design: Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…[19,20] However, the decrease in LCs with the progression to severe dysplasia [ Table 1; Figure 3] was contradictory to previous studies. [19,20] This can be explained by the observation that all the patients of the study group gave a positive history of tobacco. [21] A dose-dependent response has been demonstrated with the number of cigarettes smoked and the depletion of the LCs.…”
Section: Discussionmentioning
confidence: 59%
“…[19,20] However, the decrease in LCs with the progression to severe dysplasia [ Table 1; Figure 3] was contradictory to previous studies. [19,20] This can be explained by the observation that all the patients of the study group gave a positive history of tobacco. [21] A dose-dependent response has been demonstrated with the number of cigarettes smoked and the depletion of the LCs.…”
Section: Discussionmentioning
confidence: 59%
“…They are located between the tumor cells and in the stroma of head and neck cancers, especially in the areas of inflammatory cell infiltration. Few DCs were found in the early stage of precancerous lesions of the larynx; as the degree of dysplasia rises, more DCs infiltrate the lesion [50]. Few DCs were found in the early stage of precancerous lesions of the larynx; as the degree of dysplasia rises, more DCs infiltrate the lesion [50].…”
Section: Neoplasiamentioning
confidence: 97%
“…These antigen-presenting cells possess an outstanding capacity to initiate primary immune responses. Sprinzl et al, 65 in an immunohistochemical study of 34 precancerous lesions and seven cases of SCC of the larynx, reported a significant increase in the detection of dendritic cells as the degree of dysplasia increased. They therefore concluded that early precancerous conditions are not efficiently monitored by the immune system and may therefore develop into carcinomas without sufficient activation of cytotoxic T cells.…”
Section: Other Markersmentioning
confidence: 99%